Effect of Strategic Intervention Materials on the Learning Competencies of Learners - Dumdumaya, Chona C.; Nahial, Wenie L.; Sabacajan, Bazil T.; Morados, Alexander N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
In response to the alarming performance of the learners in the core subjects, this study aimed to improve the learning outcomes using the Strategic Intervention Materials (SIM) in Grade 6 Science subject. Two intact classes with a total of forty-six (46) Grade VI learners were used as participants of the quasi-experimental study. By random approach, the control group had 20 learners, and 26 learners in the experimental group. The effect of SIM to the performance of the struggling learners in science subject was determined using the pre-test and post-test scores of the two groups of participants. Appropriate statistical tools were used to analyse the test scores of the participants by observing the assumptions of parametric test. Results showed that the pre-test scores between the two groups of participants at the start were very comparable. However, the post test scores of the participants from the experimental and control groups were statistically different with a medium effect size. Moreover, the performance of the female participants significantly exceeded the performance of their male counterparts. This was due to the diligence of the female participants in keeping and handling of the SIM for their advantage. The researcher concluded that SIM significantly helped improve the test scores of the learners. For this, it is recommended that SIM be also applied to other learning areas in schools.